HUBUNGAN COMPUTER VISION SYNDROME DENGAN KUALITAS TIDUR PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MULAWARMAN: THE RELATIONSHIP BETWEEN COMPUTER VISION SYNDROME AND SLEEP QUALITY IN STUDENTS OF THE FACULTY OF MEDICINE, MULAWARMAN UNIVERSITY - Ningroem, Aulia Febri; Jeffry Rotinsulu, Denny; Khoma Fatmawati, Nur (ITKES Wiyata Husada Samarinda, 2024)
Computer Vision Syndrome (CVS) is a group of symptoms or eye- and vision-related problems that result from prolonged use of devices such as laptop, tablet, e-reader, and cell phone. The use of these digital devices can interfere circadian rhythm, as the blue light emitted can suppress the production of melatonin, which is often referred to as the sleep hormone. This study aims to investigate the correlation between Computer Vision Syndrome and sleep quality among students of Medicine Faculty, Mulawarman University. This study applied observational analytical method with cross–sectional approach. The data were collected through Computer Vision Syndrome Questionnaire (CVS-Q) and Pittsburgh Sleep Quality Index (PSQI) questionnaires. There were 162 students of three study programs (i.e Medicine, Dental Medicine, and Diploma-3 of Nursing) selected as research samples. It was revealed that most of the students at Medicine Faculty, Mulawarman University had a poor sleep quality (89.8%) due to Computer Vision Syndrome (CVS). Meanwhile, around 71.4% of students were not affected by Computer Vision Syndrome (CVS). The result of Chi-square test showed a correlation with p value of 0.006. In this study, it can be concluded that there is a correlation between Computer Vision Syndrome and sleep quality among students of Medicine Faculty, Mulawarman University.